2021
DOI: 10.1002/cssc.202101741
|View full text |Cite
|
Sign up to set email alerts
|

Removing the Obstacle to (−)‐Menthol Biosynthesis by Building a Microbial Cell Factory of (+)‐cis‐Isopulegone from (−)‐Limonene

Abstract: Microbial synthesis of plant‐based (−)‐menthol is of great interest because of its high demand (≈30 kiloton per year) as well as unique odor and cooling characteristics. However, this remains a great challenge due to the yet unfilled gap between (−)‐limonene and (+)‐cis‐isopulegone. Herein, the first artificial and effective system was developed for (+)‐cis‐isopulegone biosynthesis from (−)‐limonene by recruiting two bacterial enzymes to replace their inefficient counterparts from Mentha piperita, limonene‐3‐h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Previous research showed that Mentha plants use the methylerythritol phosphate pathway as the main source of C5 raw material for essential oil production and other monoterpene biosynthesis [ 23 , 24 ]. Geranyl diphosphate produces menthol and pulegone via two pathways catalyzed by a series of enzymes [ 25 ] ( Fig. 4d ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous research showed that Mentha plants use the methylerythritol phosphate pathway as the main source of C5 raw material for essential oil production and other monoterpene biosynthesis [ 23 , 24 ]. Geranyl diphosphate produces menthol and pulegone via two pathways catalyzed by a series of enzymes [ 25 ] ( Fig. 4d ).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly they used a robotics-driven semirational design strategy to identify a PpKSI variant with four active site mutations that conferred a 4.3 fold increase in activity over the WT. The final piece of the microbial menthol production puzzle was recently solved when Shou et al (2021) filled in the gap between limonene and cis -isopulegone by replacing the microbially inefficient L3H and IPDH with a bacterial P450 monooxygenase from P. putida and a bacterial IPDH from Pseudomonas aeruginosa , respectively ( Shou et al, 2021 ). Their system was able to produce 163.3 mg of cis -isopulegone from 0.54 g of limonene at a purity of 90% when analysed through GC-MS. Other work prior to limonene production has been done by Rolf et al (2020) who transformed E. coli with a plasmid containing the genes encoding the enzymes in the MVA pathway and MsLimS.…”
Section: Engineering Mint For the Futurementioning
confidence: 99%